2016
DOI: 10.13189/ujer.2016.040817
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Academic Self-efficacy of University Students in Terms of Socio-demographic Variables

Abstract: In this study whether academic self-efficacy of university students differ in terms of various socio-demographic features has been investigated. The study was conducted on 1679 students who were attending Anadolu University. In the study, the Academic Self-Efficacy Scale and Personal Information Form were used as data collection tools. In the analysis of the data, independent sample t test and one-way analysis of variance were used. The findings of the study suggested that there are significant differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
2
11
2
4
Order By: Relevance
“…In fact, in these researches, students in the most advanced years registered a higher level of academic self-efficacy. On the other hand, the results of this study contradict those obtained by a research [19] in which statistically significant differences were found taking into account the scientific area of the degree course attended by students. Students who attended degrees from Technological Sciences and Management scientific area registered higher academic self-efficacy levels compared to students attending degree courses from Agriculture, Health and Education scientific areas.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In fact, in these researches, students in the most advanced years registered a higher level of academic self-efficacy. On the other hand, the results of this study contradict those obtained by a research [19] in which statistically significant differences were found taking into account the scientific area of the degree course attended by students. Students who attended degrees from Technological Sciences and Management scientific area registered higher academic self-efficacy levels compared to students attending degree courses from Agriculture, Health and Education scientific areas.…”
Section: Resultscontrasting
confidence: 99%
“…However, sociodemographic factors such gender and age, revealed not to be differentiating factors of the academic self-efficacy level. These results are consistent with some researches [13,30] and contradictory with other researches in which male students have higher levels of academic self-efficacy [19,[31][32][33][34].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, it would be useful in the student's mental-learning efforts. Thus, different factors play different roles in improving academic self-efficacy (Satici & Can, 2016). Family, friends, school and the influence of academic transitions are very important in shaping the effectiveness of academic-self efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Akbas & Celikali, 2006;Akkus, 2003;Askar & Umay, 2001;Azar, 2010;Benzer, 2011;Chacon, 2005;Gencel, 2013;Gulec et al, 2012;Gunuc, Odabasi & Kuzu, 2012;Karakus, 2013;Kilic, 2014;Kozikoglu, 2014;Ozcan & Uzunboylu, 2012;Palmer, 2006;Seferoglu & Akbiyik, 2005;Taskin and Haciomeroglu, 2010;Uysal & Kosemen, 2013;Uzunboylu & Hursen, 2011;Yildirim & Ilhan, 2010). Besides, in the literature, lifelong learning and self-efficacy beliefs have also been studied in relation to different variables (Demirtas, Comert & Ozer, 2011;Firat Durdukoca, 2010;Guvenc, 2011;Hark Soylemez & Oral, 2013;Kutluca & Ekici, 2010;Oral & Taha, 2015;Saracaloglu, Karasakaloglu & Evin Gencel, 2010;Satici, 2013;Yenice, 2012). However, when studies conducted in Turkey are examined, it is seen that the number of studies (Ayra & Kosterelioglu, 2015;Ozciftci & Cakir, 2015;Selcuk, 2016) aimed at preservice teachers in which lifelong learning and self-efficacy beliefs are used jointly is limited.…”
Section: Introductionmentioning
confidence: 99%